Metafora Konseptual Duka pada Album Folklore Karya Taylor Swift melalui Lensa Kübler-Ross - Suci Ayustika Dewi; Gusthini, Misyi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study analyzes the use of conceptual metaphors representing the grieving process in Taylor Swift's album